Accretion flow properties of MAXI J1910-057/Swift J1910.2–0546 during its 2012–13 outburst. Issue 1 (1st January 2023) - Nath, Sujoy Kumar; Debnath, Dipak; Chatterjee, Kaushik; Jana, Arghajit; Chatterjee, Debjit; Bhowmick, Riya
Abstract: Galactic black hole candidate MAXI J1910-057/Swift J1910.2–0546 was simultaneously discovered by MAXI/GSC and Swift/BAT satellites during its first outburst in 2012. We study the detailed spectral and temporal properties of the source in a broad energy range using archival data from Swift/XRT, MAXI/GSC, and Swift/BAT satellites/instruments. Low frequency quasi periodic oscillations are observed during the outburst. The combined 1–50 keV spectra are analyzed using the transonic flow solution based Two Component Advective Flow (TCAF) model. Based on the variations of soft and hard X-ray fluxes, their hardness ratios and the variations of the spectral model fitted parameters, we find that the source has evolved through six spectral states. We interpret this spectral state evolution to be a result of the release of the leftover matter from the pile-up radius due to a sudden rise of viscosity causing a rebrightening. We show a possible configuration of the evolution of accretion flow during the outburst. From the spectral analysis with TCAF model, we estimate the probable mass of the black hole to lie in the range 6.31 M ⊙ to 13.65 M ⊙, and the source distance is estimated to be 1.9 - 8.3 kpc from transition luminosity considerations.